2008
DOI: 10.1007/s11430-008-0127-z
|View full text |Cite
|
Sign up to set email alerts
|

Migration and enrichment of trace elements of Lower Palaeozoic carbonate rock strata in Beijing

Abstract: Analyses of trace elements of the Lower Palaeozoic carbonate rock strata in Beijing show that the contents of As, Hg, F increase from primary carbonate rocks to weathered carbonate rocks and from primary carbonate rocks to the soil coexisting with carbonate rocks, but the distribution regularity of S is not obvious. In the whole weathered stages, the sorption of As is mainly affected by Fe 2 O 3 . In soil Fe 2 O 3 is also the main affecting factor of Hg enrichment. The main existing forms of Hg in primary carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 28 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…He et al [36] pointed out that the high concentration of Cd in the area was mainly distributed in exposed carbonate rocks. Ni et al [37] noted the enrichment trend of As in carbonate rocks of the Lower Paleozoic in Beijing by the symbiotic soil covering the rocks. In addition, the results of the 1:200,000 regional geochemical sweeping in Yunnan Province showed that the regions with geochemically high contents of As and Cd had good spatial coupling with widely distributed carbonates [14].…”
Section: Resultsmentioning
confidence: 99%
“…He et al [36] pointed out that the high concentration of Cd in the area was mainly distributed in exposed carbonate rocks. Ni et al [37] noted the enrichment trend of As in carbonate rocks of the Lower Paleozoic in Beijing by the symbiotic soil covering the rocks. In addition, the results of the 1:200,000 regional geochemical sweeping in Yunnan Province showed that the regions with geochemically high contents of As and Cd had good spatial coupling with widely distributed carbonates [14].…”
Section: Resultsmentioning
confidence: 99%